Historical Dynamics of Semi-Humid Evergreen Forests in the Southeast Himalaya Biodiversity Hotspot: A Case Study of the Quercus franchetii Complex (Fagaceae) - Zheng, Si-Si; Jiang, Xiao-Long; Huang, Qing-Jun; Deng, Min (Frontiers in Plant Science, 2021)
The Oligocene and Miocene are key periods in the formation of the modern topography and flora of East Asian and Indo-China. However, it is unclear how geological and climatic factors contributed to the high endemism and species richness of this region. The Quercus franchetii complex is widespread in the southeast Himalaya fringe and northern Indo-China with a long evolutionary history. It provides a unique proxy for studying the diversity pattern of evergreen woody lineages in this region since the Oligocene. In this study, we combined chloroplast (cpDNA) sequences, nuclear microsatellite loci (nSSRs) and species distribution modeling (SDM) to investigate the impacts of geological events on genetic diversity of the Q. franchetii complex. The results showed that the initial cpDNA haplotype divergence was estimated to occur during the middle Oligocene (30.7 Ma), which might have been raised by the tectonic activity at this episode to the Miocene. The nSSR results revealed two major groups of populations, the central Yunnan-Guizhou plateau (YGP) group and the peripheral distribution group when K = 2, in responding to the rapid YGP uplift during the late Miocene, which restricted gene flow between the populations in core and marginal areas. SDM analysis indicated that the distribution ranges of the Q. franchetii complex expanded northwards after the last glacial maximum, but the core distribution range in YGP was stable. Our results showed that the divergence of Q. franchetii complex is rooted in the mid-Oligocene. The early geological events during the Oligocene, and the late Miocene may play key roles to restrict seed-mediated gene flow among regions, but the pollen-mediated gene flow was less impacted. The uplifts of the YGP and the climate since LGM subsequently boosted the divergence of the populations in core and marginal areas.